Epidermal expression of I‐TAC (Cxc111) instructs adaptive Th2‐type immunity. Issue 4 (7th January 2014) - Roebrock, Kirsten; Sunderkotter, Cord; Münck, Niels‐Arne; Wolf, Marc; Nippe, Nadine; Barczyk, Katarzyna; Varga, Georg; Vogl, Thomas; Roth, Johannes; Ehrchen, Jan
Abstract : To decipher early promoters of the local microenvironment for Th2‐type immunity, we wanted to identify gene patterns that were induced by Leishmania major in the infected skin of susceptible, Th2‐prone BALB/c, but not of resistant, Th1‐prone C57BL/6 mice. We found a marked up‐regulation of the chemokine I‐TAC (Cxc111) during the first 2 d of infection in the epidermis of susceptible but not of resistant mice. Accordingly, local injection of I‐TAC (2×1 μg) in resistant mice on the first day of infection resulted in a Th2‐driven, sustained deterioration of disease and dramatically enhanced parasite levels. On the cellular level, I‐TAC decreased IL‐12 production by dendritic cells (DCs) in skin‐draining lymph nodes and by DCs in vitro . Thus, we demonstrate for the first time that epidermis‐derived I‐TAC triggers a sustained Th2‐response that determines the outcome of a complex immunological process.—Roebrock, K., Sunderkotter, C., Münck, N‐A., Wolf, M., Nippe, N., Barczyk, K., Varga, G., Vogl, T., Roth, J., Ehrchen, J. Epidermal expression of I‐TAC (Cxc111) instructs adaptive Th2‐type immunity. FASEB J. 28, 28–1724 (1734). www.fasebj.org